Material for the archaeological map of northern Afghanistan. The Murghab River ValleyAppendix A: Warwick BallAppendix B: Eric Hubbard. Issue 2 (October 2019) - Gaibov, V. A.; Koshelenko, G. A.; Trebeleva, G. V.
Abstract : The article attempts to supplement the existing database of archaeological sites of Afghanistan, based on the data presented in the seminal book by W. Ball, as well as on recently published materials of the Soviet-Afghan archaeological expedition (by I. T. Kruglikova). These data are considered at a new level, using methods of remote sensing and multi-scale topographic maps of the region previously difficult to access for studying. The object of the research was the area of the valley of the Murghab river and its two right tributaries: Chapnal (Qaisar) and Kurutu Arik. Through the comparison of the complex data it's become possible to increase significantly the number of firmly localized sites of different eras, as well as specify some issues of historical and geographical nature.